Beyond ESG Scores: Exploring Financial Mediation for Energy Sector Growth in Indonesia and Thailand - Rahmania, Thriyani; Ermawati, Wita Juwita; Suprayitno, Gendut; Thanasrivanitchai, Jul (Jurnal Aplikasi Manajemen, 2025)
Indonesia and Thailand face high disaster risks and severe environmental degradation, particularly due to unsustainable practices in the energy sector. This situation highlights the urgent need for companies to adopt sustainable business models to ensure long-term growth and resilience. The purpose of this study is to examine the impact of Environmental, Social, and Governance scores on the Sustainable Growth Rate of energy sector companies in Indonesia and Thailand, considering the mediating role of financial performance. The research employs a quantitative explanatory approach. The population consists of all energy sector companies listed in Indonesia and Thailand, with non-probability Sampling used to select companies that disclose ESG data in the Refinitiv database for the period 2019 to 2023, resulting in a total of 55 observations. Using panel data regression with a Random Effects Model and the estimation method Cluster-Robust Finite-Sample Standard Error. This estimation approach was chosen to overcome the limited number of companies and the potential for heteroscedasticity between cross-sectoral units. The results show no significant direct impact of Environmental, Social, and Governance on Sustainable Growth Rate, in contrast to financial performance, which has a significant influence. Additionally, financial performance does not have a mediating effect between Environmental, Social, and Governance pillars and Sustainable Growth Rate. This suggests that ESG implementation in these energy sectors has not yet evolved into a key strategy for sustainable growth, highlighting the need for stronger policy enforcement and comprehensive Environmental, Social, and Governance integration to improve sustainability and investor confidence.